Glyphosate input modifies microbial community structure in clear and turbid freshwater systems - Pizarro, Haydee Norma (2016)
Since it was commercially introduced in 1974, glyphosate has been one of the most commonly used herbicides in agriculture worldwide, and there is growing concern about its adverse effects on the environment. Assuming that glyphosate may increase the organic turbidity of water bodies, we evaluated the effect of a single application of 2.4 ± 0.1 mg l−1 of glyphosate (technical grade) on freshwater bacterioplankton and phytoplankton (pico, micro, and nanophytoplankton) and on the physical and chemical properties of the water. We used outdoor experimental mesocosms under clear and oligotrophic (phytoplanktonic chlorophyll a = 2.04 μg l−1; turbidity = 2.0 NTU) and organic turbid and eutrophic (phytoplanktonic chlorophyll a = 50.3 μg l−1; turbidity = 16.0 NTU) scenarios. Samplings were conducted at the beginning of the experiment and at 1, 8, 19, and 33 days after glyphosate addition. For both typologies, the herbicide affected the abiotic water properties (with a marked increase in total phosphorus), but it did not affect the structure of micro and nanophytoplankton. In clear waters, glyphosate treatment induced a trend toward higher bacteria and picoeukaryotes abundances, while there was a 2 to 2.5-fold increase in picocyanobacteria number. In turbid waters, without picoeukaryotes at the beginning of the experiment, glyphosate decreased bacteria abundance but increased the number of picocyanobacteria, suggesting a direct favorable effect. Moreover, our results show that the impact of the herbicide was observed in microorganisms from both oligo and eutrophic conditions, indicating that the impact would be independent of the trophic status of the water body.